Electrochemical Studies of C60-Fullerene Microcrystals Attached to a Solid State Electrode - Lim, Ei Bee (2001)
Electrochemistry behaviours of C₆₀ attached with physical method: solvent casting and mechanically attachment, to various solid-state electrode surfaces (gold, glassy carbon and platinum) were studied in aqueous and non-aqueous solution containing a variety of doping cations such as Group I alkali-metal cations and quatemaI)'-ammonium R4N+. Electroreduction and reoxidation of microcrystalline C₆₀ in 0.1 M TBAPF₆/ACN showed one to four pairs, characteristic solid state current-potential curve, with only first and second pairs appeared to be stable and reversible. In contact with 0.1 M TBAPF₆/ACN, the large peak separation and small maximum at reverse scan observed with cyclic voltammetric experiments, as well as the current-time transients obtained in chronoamperometric experiments produce evidence of nucleation and growth (N&G) processes at the electrolytesolid- electrode interface. C60 cast onto glassy carbon or gold electrodes showed very different results of cyclic voltammetry (CV), chronocoulometry (CC), and chronoamperometry (CA) in aqueous and non-aqueous solutions. With the presence of alkali-metal cations in aqueous electroyte, MnC₆₀ (M = LI⁺, Na⁺, K⁺, R⁺, Cs⁺, n = 1 to 6) was formed at the end of potential scan, and the loss of faradaic activity when oxidizing MnC60 at reverse of potential scan indicated the formation of non-electroactive and irreversible species. In aqueous solution, CV results showed a parallel shift in reduction peak position as the sizes of cation increased. A glassy carbon electrode modified by C60 coat was used to mediate the oxidation of cysteine in contact with an aqueous electrolyte containing potassium cation. Under conditions of cyclic voltammetry, the potential of cysteine is lowered by approximate 100 m V and current is enhanced significantly relative to the situation prevailing when a bare glassy carbon electrode is used. Mediation also occurs when the potential range covered include that of Cw/C60n- redox couples.